Relationship of cell-mediated cytotoxicity against melanoma cells to prognosis in melanoma patients. - Hershey, P. (Nature Publishing Group, 1978)
The cell-mediated cytotoxicity (CMC) of blood mononuclear cells against cultured human melanoma cells was measured in patients after surgical removal of localized melanoma, at a time when they were considered on clinical grounds to be free of melanoma. It was found that the distribution of CMC values against melanoma cells in melanoma patients was different from that in control subjects, and several sub-populations of melanoma patients were evident on the basis of these measurements. No difference in distribution of CMC values was found against non-melanoma cells, which suggested the changes were specific for melanoma. The proportion of patients with recurrence of melanoma was compared between the patient groups with low, normal or high CMC values against cultured melanoma cells after surgery. Analysis for periods extending to 2 years showed that patients with low CMC values after surgery had a significantly higher incidence of recurrence from melanoma than patients with normal or high CMC values. These results suggest there may be a sub-group of melanoma patients who have intrinsically low CMC against melanoma cells, and that this may be an important predisposing factor in the development of recurrent melanoma.